(untitled) (Washington, D.C, 2000)
Designed to fill the existing gap between simple introductory texts and very advanced reviews of major virus families, Principles of Virology introduces upper-level undergraduates, graduate students, and medical students to all aspects of virology
Keywords: Virology,Vi rút; Methods,Phương pháp